Determination of the most significant indicators of the preparedness of young men, representatives of various methods of swimming, which limit their sporting achievements - Політько, Олена; Шутєєв, Вячеслав (Slobozhanskyi Herald of Science and Sport, 2019)
Elena Politko & Viacheslav Shutieiev Purpose: the establishment of the most significant selection criteria for swimmers aged 14–16 years specializing in various swimming methods, which limit their sporting achievements. Material & Methods: analysis and synthesis of scientific and methodical literature, pedagogical observation, testing, anthropometric measurements, methods of mathematical statistics. Results: the scientific knowledge about modern model characteristics of a constitution and physical preparedness of the young swimmers specializing in various ways of swimming is added. Established significant selection criteria, allowing to identify the most gifted athletes, to orient their training for a specific competitive distance. Conclusion: obtained results can be recommended for use in the work of swimming coaches to improve the quality of selection and sports orientation of young athletes on the choice of swimming and assess their prospects.